The Three Must-Get-Theres Based on the Novel by Alexandre Dumas - Nelissen, Maud (Max Linder: Les longs métrages américains, 2014)
The career of influential comedian Max Linder was nearing its end when he directed and starred in this burlesque of Douglas Fairbanks' "Three Musketeers". As Dart-in-Again, Linder plays an hilarious spoof of the Fairbanks character. He is a peasant's son who rides his donkey, Jazbo, to Paris to make his fortune. Upon his arrival, he meets the three Must-Get-Theres - Walrus (Jack Richardson), Octopus (Charles Metzetti) and Porpoise (Clarence Werpz). They all battle the forces of the evil Duke of Rich-Lou (Bull Montana). Dart-in-Again comes to the aid of the Queen (Catherine Rankin), and her seamstress, Connie (Jobyna Ralston, Harold Lloyd's future co-star). He retrieves the Queen's brooch from her lover, Bunkumin (Harry Mann) and saves her honor. For his heroic acts, Dart-In-Again is rewarded by the King (Frank Cooke), who makes him a full member of the Must-Get-Theres. He also weds Connie and all ends well. Unfortunately, things didn't end so well for Linder in real life - three years later, he and his wife would commit suicide because his career was in a shambles. [www.allmovie.com]